Quality of Life in Children and Adolescents With Learning Problems: Development and Validation of the LD/QOL15 Scale. - Waber, Deborah P.; Boiselle, Ellen C.; Forbes, Peter W.; Girard, Jonathan M.; Sideridis, Georgios D. (Journal of Learning Disabilities)
Learning problems (LP) can have wider implications than the academic deficits per se. The goal of the present series of studies was to develop a reliable and valid quality-of-life measure targeted to children and adolescents with LP. In Study 1, using a 35-item questionnaire, we surveyed 151 parents/guardians of children referred for assessment of learning disorders. Exploratory factor analysis identified a three-factor model: Academic Performance, School Understanding, and Child/Family Psychological. These factors were validated against standardized measures of academic achievement and psychosocial functioning. The questionnaire was then reduced to 15 items—the LD/QOL15 —and administered to a community sample of 325 parents/guardians of children in Grades 1 to 8 (Study 2). The three-factor model was verified with confirmatory factor analysis. Comparison of general education (n = 232) and LP (n = 93) groups within the community sample documented substantial group differences (p < .0001), with the LP group having higher mean scores. These differences were larger for older students (Grades 5–8) than younger students (Grades 1–4; p < .01). The LD/QOL15 is a brief and reliable measure that is valid to assess quality of life and, potentially, outcomes in children and adolescents with LP.